POEMS AND YOUNG READERS: A PROPOSAL FOR THE CLASSROOM - Silva Barbosa, Gislene Aparecida da; Mello Miranda, Katia Rodrigues [UNESP] (Fundacao Univ Tocantins, 2020)
In this text there is a proposal for the practice of reading poems for the literary literacy of adolescents in the final years of elementary school. The goal is to share with basic education teachers and undergraduate students some possibilities of teaching reading to develop students' literary competence, valuing the multiplicity of meanings present in the poetic text - which is not always in the classroom. Through the practice of cumulative reading (COSSON, 2020) associated with reading strategies (GIROTTO; SOUZA, 2010), a reading suggestion is presented with the act of reading poems; with the student's response to the reading of poetic texts; and collaborative interpretation of texts. This activity is expected to contribute to reading practices at school and literary literacy for young people.
Keywords: Literary literacy; Poems; Cumulative reading; Reading strategies